Interactions of 172 plant extracts with human organic anion transporter 1 (SLC22A6) and 3 (SLC22A8): a study on herb-drug interactions - Hang Lu; Zhiqiang Lu; Xue Li; Gentao Li; Yilin Qiao; Robert P. Borris; Youcai Zhang (PeerJ, 2017)
Background Herb-drug interactions (HDIs) resulting from concomitant use of herbal products with clinical drugs may cause adverse reactions. Organic anion transporter 1 (OAT1) and 3 (OAT3) are highly expressed in the kidney and play a key role in the renal elimination of substrate drugs. So far, little is known about the herbal extracts that could modulate OAT1 and OAT3 activities. Methods HEK293 cells stably expressing human OAT1 (HEK-OAT1) and OAT3 (HEK-OAT3) were established and characterized. One hundred seventy-two extracts from 37 medicinal and economic plants were prepared. An initial concentration of 5 µg/ml for each extract was used to evaluate their effects on 6-carboxylfluorescein (6-CF) uptake in HEK-OAT1 and HEK-OAT3 cells. Concentration-dependent inhibition studies were conducted for those extracts with more than 50% inhibition to OAT1 and OAT3. The extract of Juncus effusus, a well-known traditional Chinese medicine, was assessed for its effect on the in vivo pharmacokinetic parameters of furosemide, a diuretic drug which is a known substrate of both OAT1 and OAT3. Results More than 30% of the plant extracts at the concentration of 5 µg/ml showed strong inhibitory effect on the 6-CF uptake mediated by OAT1 (61 extracts) and OAT3 (55 extracts). Among them, three extracts for OAT1 and fourteen extracts for OAT3 were identified as strong inhibitors with IC50 values being <5 µg/ml. Juncus effusus showed a strong inhibition to OAT3 in vitro, and markedly altered the in vivo pharmacokinetic parameters of furosemide in rats. Conclusion The present study identified the potential interactions of medicinal and economic plants with human OAT1 and OAT3, which is helpful to predict and to avoid potential OAT1- and OAT3-mediated HDIs.